2016
DOI: 10.1037/vio0000016
|View full text |Cite
|
Sign up to set email alerts
|

TakeCARE, a video bystander program to help prevent sexual violence on college campuses: Results of two randomized, controlled trials.

Abstract: Objective The present research reports on two randomized controlled trials evaluating TakeCARE, a video bystander program designed to help prevent sexual violence on college campuses. Method In Study 1, students were recruited from psychology courses at two universities. In Study 2, first-year students were recruited from a required course at one university. In both studies, students were randomly assigned to view one of two videos: TakeCARE or a control video on study skills. Just before viewing the videos,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 30 publications
6
56
0
1
Order By: Relevance
“…Coefficient alpha was .85 and .89 at baseline and follow-up, respectively. Consistent with theory and research on determinants of bystander behavior (Banyard et al, 2007; Jouriles et al, 2016), helpful bystander behavior and bystander self-efficacy (using a 5-item measure of bystander self-efficacy adapted from Banyard, Plante, & Moynihan, 2005) were correlated positively at baseline, r = .17, p < .001.…”
Section: Methodssupporting
confidence: 70%
See 2 more Smart Citations
“…Coefficient alpha was .85 and .89 at baseline and follow-up, respectively. Consistent with theory and research on determinants of bystander behavior (Banyard et al, 2007; Jouriles et al, 2016), helpful bystander behavior and bystander self-efficacy (using a 5-item measure of bystander self-efficacy adapted from Banyard, Plante, & Moynihan, 2005) were correlated positively at baseline, r = .17, p < .001.…”
Section: Methodssupporting
confidence: 70%
“…One to two months later, all students completed follow-up questionnaires on helpful bystander behavior. Results of each trial indicated that those who viewed TakeCARE reported engaging in more helpful bystander behavior during the follow-up period than those in the control condition (Kleinsasser et al, 2015; Jouriles et al, 2016). These three trials included students from two different universities and at different time points during their college careers, although all three samples were predominantly White; students also viewed TakeCARE under highly controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bullying is a group phenomenon and we know from previous research that bystanders play a crucial role in maintaining or limiting the level of bullying in school (Salmivalli, Poskiparta, Strohmeier, & Noam, 2012). Bystander intervention has also been useful for other areas of violence (Coker et al, 2014; Jouriles et al, 2015)…”
Section: Discussionmentioning
confidence: 99%
“…Prevention of sexual assault is important, and preventive programmes have received some empirical support (Jouriles et al, 2016). This study implies that strategies should include targeted efforts against intoxicated assault.…”
Section: Discussionmentioning
confidence: 99%